Redução do uso de água, rendimento e qualidade de grãos de dois cultivares de arroz irrigado em função de épocas de supressão da irrigação - Londero, Guilherme Pilar (2014)
The irrigation of the rice crop is essential for good plant growth, assisting in achieving high grain yield levels. However, it results in large water volume used, thus the efficiency of water use is a major challenge to the sustainability of the crop. In this matter, early irrigation withholding can be considered an option for saving water. However, this practice can prejudice the quality of the crop, in yield and grain quality. In rice cultivars with large panicles, as in the case of hybrid rice, early withholding may be reflected in the quality of the grains from the bottom of the panicle, due to the difficulty of kernel filling in this region. Research was conducted during the growing seasons 2011/12 and 2012/13 , in order to verify the effect of anticipated moments of withholding irrigation on yield and water use efficiency ( Chapter II ) , and grain quality ( Chapter III ) of two rice cultivars . The experiments were conducted in the floodplains of the Departamento de Fitotecnia of the Federal University of Santa Maria (UFSM), using the experimental design of randomized blocks with four replications. Each experiment was composed of the factorial design appropriate to the factorsconsidered. Early withholding irrigation reduces the volume of water used in the rice crop, but depending on the moment and the cultivar, it can reduce productivity. For withholding irrigation performed before the recommended time it should be taken into account the cultivar, soil type and possible rainfall after the end of irrigation. Harvests with lower humidity than that recommended by research show a reduction in milling quality. Early withholding does not affect the milling quality, translucency, opaque and chalky grains; however, there was no difference in quality between the studied cultivars.